Horizontal methods for molecular biomarker analysis. Methods of analysis for the detection of genetically modified organisms and derived products. Real-time PCR methods for the detection of CaMV and Agrobacterium Ti-plasmid derived DNA sequences Part 7, (4th January 2023) - British Standards Institution,
No abstract available